Universe of the mind : a semiotic theory of culture - Lotman, Jurij Mihajlovič (I. B. Tauris, 2001)
Universe of the Mind addresses three main areas: meaning and text, culture, and history. The result is a full-scale attempt to demonstrate the workings of the semiotic space or intellectual world. Part One is concerned with the ways that texts generate meaning. Part Two addresses Lotman’s central idea of the semiosphere―the domain in which all semiotic systems can function―presented through an analogy with the global biosphere. Part Three focuses on semiotics from the point of view of history.